A Novel Nomogram for Predicting Postoperative Liver Failure After Major Hepatectomy for Hepatocellular Carcinoma - Lei, Zhengqing; Cheng, Nuo; Si, Anfeng; Yang, Pinghua; Guo, Guangmeng; Ma, Weihu; Yu, Qiushi; Wang, Xuan; Cheng, Zhangjun (Frontiers in Oncology, 2022)
Purpose: Post-hepatectomy liver failure (PHLF) is the most common cause of mortality after major hepatectomy in hepatocellular carcinoma (HCC) patients. We aim to develop a nomogram to preoperatively predict grade B/C PHLF defined by international Study Group on Liver Surgery Grading (ISGLS) in HCC patients undergoing major hepatectomy. Patients and Methods: The consecutive HCC patients who underwent major hepatectomy at the Eastern Hepatobiliary Surgery Hospital between 2008 and 2013 severed as a training cohort to develop preoperative nomogram, and patients from other 2 hospitals comprised an external validation cohort. Least absolute shrinkage and selection operator (LASSO) logistic regression was applied to identify preoperative predictors of grade B/C PHLF. Multivariable logistic regression was utilized to establish a nomogram model. Internal and external validation were used to verified the performance of the nomogram. The accuracy of the nomogram was also compared with the conventional scoring models, including MELD, ALBI, and Child-Pugh score. Results: A total of 880 patients underwent major hepatectomy (668 in the training cohort and 192 in the validation cohort) was enrolled in this study. The independent risk factors of grade B/C PHLF were age, gender, prothrombin time, total bilirubin, and CSPH, which were incorporated into the nomogram. Good prediction discrimination was achieved in training (AUROC: 0.73) and validation (AUROC: 0.72) cohorts. Calibration curve also showed good agreement in both training and validation cohort. The nomogram has a better performance than the 3 conventional models. Conclusion: The proposed nomogram showed more accurate ability to individually predict grade B/C PHLF after major hepatectomy in HCC patients than MELD, ALBI, and Child-Pugh score.